Government Strategies for Stunting Reduction to Achieve The Sustainable Development Goals in North Aceh Regency - Anwar, Anwar; Supriyanto, Sapto; Samtono, Samtono (Jurnal Impresi Indonesia, 2025)
This study aims to explore the government’s strategies in addressing stunting in North Aceh Regency and examine how policy implementation is understood and practiced within the region’s socio-cultural context. Stunting remains a critical public health issue in North Aceh, with prevalence rates exceeding the national average, highlighting the need for more contextualized and participatory approaches. A qualitative case study design was employed, with data collected through semi-structured interviews involving 25 key informants, participant observation in community nutrition and health programs, and document analysis of local policy reports and official records. Informants were selected using purposive and snowball sampling techniques, including health cadres, public health officers, local government officials, community leaders, and mothers of under-five children. Thematic analysis based on Miles and Huberman’s interactive model was used to analyze the data. Four major themes emerged: (1) cultural perceptions linking rice as the primary indicator of nutritional adequacy, (2) limited human resource capacity and sectoral coordination, (3) a gap between nutrition education and actual consumption practices, and (4) weak monitoring systems and case follow-up mechanisms. These findings underscore the importance of aligning policy implementation with local values and social structures. This study contributes to the development of policy implementation and social-ecological theories in public health contexts. Practical implications include the need for culturally adaptive nutrition programs and stronger community-based monitoring systems. Future research is recommended to adopt participatory approaches for developing more responsive interventions tailored to local community needs.